Abdominal tuberculosis: a surgical perplexity - Vagholkar, Ketan R.; Chandrashekhar, Shantanu; Vagholkar, Suvarna (International Journal of Advances in Medicine, 2018)
Abdominal tuberculosis is one of the most challenging forms of extra pulmonary tuberculosis. The diagnosis of the disease itself poses the greatest challenge due to the variability of presentation. Clinical presentations in various forms with conflicting results on a multitude of haematological, immunological and radiological tests causes a lot of confusion in interpreting and correlating the symptoms to arrive at a diagnosis. This adds to the perplexity in surgical management of this complex disease especially in an era where AIDS has added to the problems. Having arrived at a diagnosis, chemotherapy is the mainstay of treatment. Surgery is indicated when the response to medical therapy is poor or complications supervene. Deciding the optimum procedure is again a major issue. Understanding the pathophysiology therefore is pivotal in making a value decision. The article briefly outlines the approach to this surgical perplexity.